Penghambatan Senyawa di dalam Kopi terhadap Protein Fibronektin dan Protein Shroom: Kajian Gangguan Neurulasi Primer Secara in Silico - Santoso, Novian Budi; Susanto, Susanto; Adrianto, Hebert; Kharisma, Viol Dhea (Poltekkes Kemenkes Tanjung Karang, 2022)
Coffee drinking habits exist in Indonesian culture. Coffee as the primary source of caffeine is here the effect of embryotoxicity on paralysis, wrong brain. The brain is going on so that the body is a curiosity. Fibronectin and shroom proteins play in the primary stacking cage, which is the seasoning of the nerve roof. This study aimed to predict molecular inhibition of compounds in coffee in fibronectin protein and shroom protein in silica. The research method used samples of ligands and target proteins from the PubChem database and protein databank, then analyzed using PyRx, Discovery Studio, and PyMol software. The results of the study of literature there are five compounds in coffee. As a result of molecular docking simulation analysis, caffeine compounds (CID 2519) had lower total binding energy (-9.9 kcal/mol) in other combinations in fibronectin and shroom proteins. There are six residues of the amino acid fibronectin and 5 in shroom with caffeine. There are chemical bonds provided for caffeine compounds consisting of hydrophobic, alkyl, Van der Waals, and electrostatic. Caffeine can inhibit fibronectin and shroom protein activity and in vitro and in vivo tests to validate bioinformatics results.